RANCANGAN KONTROL PINTU RUANG SCIENCE ART MUSIC STUDIO DI SEKOLAH TINGGI PENERBANGAN INDONESIA - Toni Dwi Tindak Hidayanto; KGS. M. Ismail; Usman Sumantri (Politeknik Penerbangan Indonesia Curug, 2017)
Control of Science Art Studio Room which is called (SAM Studio) is intended as one of security helping tools in SAM room studio at STPI (Indonesian State Aviation School) Curug. The matter that often we faced is the shortfall of responsibility of the studio room’s borrower and that sometimes there were lost and broken items without further action because of the mass amount of borrowers in the room of SAM studio. Seeing this, the writer has an idea to make a project that could give solutions towards the problems that take place. To design the tools that we hope to be utilized by STPI Curug, the writer searched for information from many sources whether like book references or websites regarding theories and programs that related to the project that is going to be made. This project consists of Microcontroller that is Arduino uno as the brain of the program that is being used, module data logger as the reciever of the data’s activity, other than that keypad 3 can be found as the manual lock from the shortest range with the already specified password, and also other components such as LCD 162, relay modul, modul I2C converter, and of course the transformator as power supply’s source of the project and also the magnetic lock that will be used to lock the room of SAM studio